Spatial distribution of air temperature and relative humidity in the greenhouse as affected by external shading in arid climates - Hesham A. Ahmed; Yu-xin TONG; Qi-chang YANG; Abdulellah A. Al-Faraj; Ahmed M. Abdel-Ghany (Journal of Integrative Agriculture)
The effect of external roof shading on the spatial distribution of air temperature and relative humidity in a greenhouse (Tin and RHin) was evaluated under the arid climatic conditions of Riyadh City, Saudi Arabia. Two identical, evaporatively-cooled, single-span greenhouses were used in the experiment. One greenhouse was externally shaded (Gs) using a movable black plastic net (30% transmissivity), and the other greenhouse was kept without shading (Gc). Strawberry plants were cultivated in both greenhouses. The results showed that the spatial distribution of the Tin and RHin was significantly affected by the outside solar radiation and evaporative cooling operation. The regression analysis showed that when the outside solar radiation intensity increased from 200 to 800 W m–2, the Tin increased by 4.5°C in the Gc and 2°C in the Gs, while the RHin decreased by 15% in the Gc and 5% in the Gs, respectively. Compared with those in the Gc, more uniformity in the spatial distribution of the Tin and RHin was observed in the Gs. The difference between the maximum and minimum Tin of 6.4°C and the RHin of 10% was lower in the Gs than those in the Gc during the early morning. Around 2°C difference in the Tin was shown between the area closed to the exhausted fans and the area closed to the cooling pad with the external shading. In an evaporatively-cooled greenhouse in arid regions, the variation of the Tin and RHin in the vertical direction and along the sidewalls was much higher than that in the horizontal direction. The average variation of the Tin and RHin in the vertical direction was 5.2°C and 10% in the Gc and 5.5°C and 13% in the Gs, respectively. The external shading improved the spatial distribution of the Tin and RHin and improved the cooling efficiency of the evaporative cooling system by 12%, since the transmitted solar radiation and accumulated thermal energy in the greenhouse were significantly reduced.